The fat thumb: Using the thumb's contact size for single-handed mobile interaction - BORING, Sebastian (Institutional Knowledge at Singapore Management University, 2012)
Modern mobile devices allow a rich set of multi-finger interactions that combine modes into a single fluid act, for example, one finger for panning blending into a two-finger pinch gesture for zooming. Such gestures require the use of both hands: one holding the device while the other is interacting. While on the go, however, only one hand may be available to both hold the device and interact with it. This mostly limits interaction to a single-touch (i.e., the thumb), forcing users to switch between input modes explicitly. In this paper, we contribute the Fat Thumb interaction technique, which uses the thumb’s contact size as a form of simulated pressure. This adds a degree of freedom, which can be used, for example, to integrate panning and zooming into a single interaction. Contact size determines the mode (i.e., panning with a small size, zooming with a large one), while thumb movement performs the selected mode. We discuss nuances of the Fat Thumb based on the thumb’s limited operational range and motor skills when that hand holds the device. We compared Fat Thumb to three alternative techniques, where people had to precisely pan and zoom to a predefined region on a map and found that the Fat Thumb technique compared well to existing techniques.